Ionic liquid inhibitor as well as preparation method and application thereof

By adding silicone nanomaterials to the ionic liquid inhibitor, the problem of difficult to take into account the temperature resistance and inhibitory properties of existing inhibitors at high temperatures is solved, and efficient well wall stability and polymer temperature resistance are achieved to meet the needs of deep drilling.

CN119709141APending Publication Date: 2025-03-28CHINA NAT PETROLEUM CORP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411684872.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

The existing ionic liquid inhibitors are difficult to take into account both the temperature resistance and inhibition properties at high temperatures, and cannot effectively solve the problems of well wall instability and polymer degradation in deep drilling.

Method used

By designing the preparation raw materials for ionic liquid inhibitors, silicone nanomaterials are innovatively added, and their high heat conduction and resistance to high temperature are used to synergize the anti-high temperature effect and enhance the temperature resistance and inhibitory properties of the inhibitors.

Benefits of technology

The prepared ionic liquid inhibitor has good thermal stability and high inhibition rate, which can effectively inhibit the hydration expansion and dispersion of clay minerals, improve the temperature resistance of polymers, and meet the needs of deep drilling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119709141A_ABST
    Figure CN119709141A_ABST
Patent Text Reader

Abstract

The invention provides an ionic liquid inhibitor as well as a preparation method and application thereof. The ionic liquid inhibitor is prepared from the following raw materials: amino acid, an acidic compound and an organic silicon nano material; the acidic compound comprises H2SO4; the molar ratio of the amino acid to the acidic compound is 1: (1-1.5); the ratio of the amount of substance of the amino acid to the mass of the organic silicon nano material is 1mol: (3-6) g. The preparation raw materials of the ionic liquid inhibitor are designed, the organic silicon nano material is further used, and the temperature resistance and the inhibition property of the ionic liquid inhibitor are synchronously enhanced through the synergistic high-temperature-resistant effect of the organic silicon nano material and the ionic liquid.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of water-based drilling fluid materials, and specifically relates to an ionic liquid inhibitor and a preparation method and application thereof, and more specifically relates to an ionic liquid inhibitor for high-temperature resistant water-based drilling fluid and a preparation method and application thereof. Background Art

[0002] With the gradual increase in the development of deep and ultra-deep oil and gas resources, higher temperature formations will be encountered during drilling. Polymer materials are prone to degradation and failure at high temperatures, resulting in a sharp deterioration in the performance of drilling fluids. Therefore, how to improve the temperature resistance of polymers has become one of the hot topics in deep and ultra-deep well research. In addition, in the process of deep oil extraction, drilling problems such as well wall instability and collapse caused by hydration expansion and hydration dispersion of clay minerals are often encountered, which may even lead to drilling failure in severe cases. In the final analysis, the temperature resistance and inhibition of existing inhibitors cannot simultaneously meet the requirements of deep drilling.

[0003] How to solve the problem of wellbore instability caused by deep formation clay hydration, that is, to collaboratively solve the temperature resistance and inhibition of existing inhibitors, is of great significance for the smooth progress of deep drilling work. Ionic liquid inhibitors are a new type of inhibitor with excellent performance, but it is difficult to effectively balance the temperature resistance and inhibition of existing ionic liquids. The temperature resistance and inhibition of ionic liquids still need to be further coordinated and improved. Based on this, the research on a temperature-resistant and excellent-performance ionic liquid inhibitor for water-based drilling fluids is of great significance.

[0004] Since the wellbore temperature is mainly concentrated in the static fluid of the formation, it cannot be transmitted to the ground in time through the drilling fluid, so the polymer is exposed to high temperature for a long time and degrades. Therefore, if the temperature of the formation can be exported in time, that is, the thermal conductivity of the polymer can be improved, the temperature resistance of the polymer and the drilling fluid can be improved to a great extent.

[0005] Therefore, how to provide an ionic liquid inhibitor that has both temperature resistance and inhibition, thermal conductivity, and can meet the requirements of deep drilling has become a technical problem that needs to be solved urgently. Summary of the invention

[0006] In view of the shortcomings of the prior art, the purpose of the present invention is to provide an ionic liquid inhibitor (Asp) and a preparation method and application thereof. In the present invention, by designing the raw materials for preparing the ionic liquid inhibitor, further using organic silicon nanomaterials, and synergistically improving the high temperature resistance of the organic silicon nanomaterials and ionic liquids, the temperature resistance and inhibitory properties of the ionic liquid inhibitor are simultaneously enhanced.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] In a first aspect, the present invention provides an ionic liquid inhibitor (Asp), wherein the raw materials for preparing the ionic liquid inhibitor include amino acids, acidic compounds and organosilicon nanomaterials;

[0009] The acidic compound includes H2SO4;

[0010] The molar ratio of the amino acid to the acidic compound is 1:(1-1.5);

[0011] The ratio between the amount of the amino acid and the mass of the organosilicon nanomaterial is 1 mol:(3-6) g.

[0012] Silicone nanomaterials contain a large number of silicon-oxygen chains. The bond energy of silicon-oxygen is higher than that of carbon-carbon bonds, carbon-hydrogen bonds, etc., and is not easily destroyed at high temperatures. Therefore, silicone nanomaterials have better and more effective high-temperature resistance in drilling fluids.

[0013] In the present invention, the raw materials for preparing the ionic liquid inhibitor are designed, and nano-organic silicon materials with high thermal conductivity are innovatively added during the preparation process. The synergistic high-temperature resistance of the organosilicon nano-materials and the ionic liquids are used to simultaneously enhance the temperature resistance and inhibitory properties of the ionic liquid inhibitor. The prepared ionic liquid inhibitor has good thermal stability and can be directly used in temperature-resistant water-based drilling fluids.

[0014] In the present invention, by controlling the dosage of amino acid, concentrated sulfuric acid and organosilicon nanomaterials within a specific range, an ionic liquid inhibitor Asp having both temperature resistance, inhibition and thermal conductivity and meeting the requirements of deep drilling is prepared. If the molar ratio of amino acid to concentrated sulfuric acid is too small, that is, the dosage of concentrated sulfuric acid is too much, the chemical reaction is violent and difficult to produce; if the molar ratio of amino acid to concentrated sulfuric acid is too large, that is, the dosage of concentrated sulfuric acid is too small, the reaction is not complete, resulting in waste of materials; if the ratio between the amount of amino acid and the mass of organosilicon nanomaterials is too small, that is, the dosage of organosilicon nanomaterials is too large, the inhibition performance cannot reach the design; if the ratio between the amount of amino acid and the mass of organosilicon nanomaterials is too large, that is, the dosage of organosilicon nanomaterials is too small, the temperature resistance of the system cannot reach the expected level, and the comprehensive performance is poor.

[0015] In the present invention, the molar ratio of the amino acid to the acidic compound can be 1:1, 1:1.05, 1:1.1, 1:1.15, 1:1.2, 1:1.25, 1:1.3, 1:1.35, 1:1.4, 1:1.45 or 1:1.5, etc.

[0016] The ratio between the amount of the amino acid substance and the mass of the organosilicon nanomaterial can be 1 mol:3g, 1 mol:3.3g, 1 mol:3.6g, 1 mol:3.8g, 1 mol:4g, 1 mol:4.2g, 1 mol:4.4g, 1 mol:4.6g, 1 mol:4.8g, 1 mol:5g, 1 mol:5.2g, 1 mol:5.5g, 1 mol:5.8g or 1 mol:6g, etc.

[0017] It should be noted that, in the present invention, H2SO4 is provided by concentrated sulfuric acid with a mass concentration of 92-98%, and the mass concentration of H2SO4 in the concentrated sulfuric acid can be 92%, 93%, 94%, 95%, 96%, 97% or 98%, etc.

[0018] The following are preferred technical solutions of the present invention, but are not intended to limit the technical solutions provided by the present invention. Through the following preferred technical solutions, the objectives and beneficial effects of the present invention can be better achieved and realized.

[0019] As a preferred technical solution of the present invention, the amino acids include (L-aspartic acid) and / or (Methionine).

[0020] As a preferred technical solution of the present invention, the organosilicon nanomaterial includes an organosilicon nanomaterial selected from graphene oxide modified by a silane coupling agent, preferably graphene oxide modified by KH570 and / or graphene oxide modified by KH550.

[0021] As a preferred technical solution of the present invention, the molar ratio of the amino acid to the acidic compound is 1:1.5;

[0022] As a preferred technical solution of the present invention, the ratio between the amount of the amino acid substance and the mass of the organosilicon nanomaterial is 1 mol:6 g.

[0023] In a second aspect, the present invention provides a method for preparing the ionic liquid inhibitor Asp for temperature-resistant water-based drilling fluid as described in the first aspect, the preparation method comprising the following steps:

[0024] After the amino acid and the solvent are mixed, an acidic compound is added thereto for neutralization reaction. After the temperature of the reaction system is raised to the neutralization reaction temperature, an organosilicon nanomaterial is added thereto for reaction to obtain the ionic liquid inhibitor Asp.

[0025] As a preferred technical solution of the present invention, the solvent is water.

[0026] Preferably, the ratio between the amount of amino acid substance and the volume of the solvent is 1 mol:(180-240) mL, for example, it can be 180 mL, 185 mL, 190 mL, 195 mL, 200 mL, 205 mL, 210 mL, 215 mL, 220 mL, 225 mL, 230 mL, 235 mL or 240 mL, etc.

[0027] As a preferred technical solution of the present invention, the temperature of the neutralization reaction is 70-90°C (for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C or 90°C, etc.), preferably 80°C.

[0028] Preferably, the neutralization reaction time is 12-24 h (for example, it can be 12 h, 13 h, 14 h, 15 h, 16 h, 17 h, 18 h, 19 h, 20 h, 21 h, 22 h, 23 h or 24 h, etc.), and more preferably 12 h.

[0029] The invention designs the temperature and time of the neutralization reaction and controls the temperature and time of the neutralization reaction within a specific range, thereby preparing an ionic liquid inhibitor Asp for temperature-resistant water-based drilling fluid with excellent performance.

[0030] As a preferred technical solution of the present invention, the reaction further includes a post-treatment step, and the post-treatment method includes: washing and drying.

[0031] Preferably, the solvent used in the washing process comprises ethyl acetate.

[0032] Preferably, the washing is performed 4-6 times, for example, 4 times, 5 times or 6 times.

[0033] In a third aspect, the present invention provides a use of the ionic liquid inhibitor as described in the first aspect, wherein the ionic liquid inhibitor is used to prepare a temperature-resistant water-based drilling fluid.

[0034] Preferably, the mass percentage of the ionic liquid inhibitor in the warm water-based drilling fluid is 0.1-1.2%, for example, it can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%, etc.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The present invention designs the raw materials for preparing the ionic liquid inhibitor, further uses organosilicon nanomaterials, and controls the dosage of amino acids, acidic compounds and organosilicon nanomaterials within a specific range. Through the synergistic effect of organosilicon nanomaterials and ionic liquids to increase the temperature, the temperature resistance and inhibitory properties of the ionic liquid inhibitor are simultaneously enhanced, and a ionic liquid inhibitor having both temperature resistance and inhibitory properties, good thermal stability and high water solubility is prepared.

[0037] (2) When the mass addition amount of the ionic liquid inhibitor provided by the present invention is 1% in the temperature-resistant water-based drilling fluid, the inhibition rate can be as high as 91.95%, the linear expansion rate is reduced by 40.94% compared with that in clear water, the temperature resistance can be as high as 246°C, and the hydration expansion and hydration dispersion of clay minerals can be effectively inhibited.

[0038] (3) The ionic liquid inhibitor provided by the present invention has simple preparation steps, low raw material cost, mild reaction conditions, easy control, and can be used for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The infrared spectra of the soil samples treated with Asp and the soil samples treated with pure water are shown in FIG. 6 , wherein Asp is provided by Example 6 of the present invention;

[0040] Figure 2 Thermogravimetric analysis diagrams of soil samples treated with Asp and soil samples treated with pure water, where Asp is provided by Example 6 of the present invention;

[0041] Figure 3 The particle size distribution diagrams of unhydrated soil samples treated with Asp, hydrated soil samples treated with Asp, unhydrated soil samples, and hydrated soil samples, wherein Asp is provided by Example 6 of the present invention;

[0042] Figure 4 It is the linear expansion coefficient of the soil sample treated with pure water, the soil sample treated with 1.0% KCl, the soil sample treated with 0.1% Asp, the soil sample treated with 0.2% Asp, the soil sample treated with 0.3% Asp, the soil sample treated with 0.5% Asp, and the soil sample treated with 1.0% Asp, where Asp is provided by Example 6 of the present invention.

[0043] Figure 5 is the linear expansion rate of the soil sample treated with 6.0% KCl and the soil sample treated with 1.0% Asp, and Asp is provided by Example 6 of the present invention. DETAILED DESCRIPTION

[0044] The technical solution of the present invention is further described below in conjunction with the accompanying drawings and through specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0045] The sources of some components in the following examples and comparative examples are as follows:

[0046] Concentrated sulfuric acid: mass concentration is 98%;

[0047] Silane coupling agents KH570 and KH550: purchased from Yunsheng Chemical (Shandong) Co., Ltd., with an effective content of 98%;

[0048] Graphene oxide: purchased from Shandong Yuhuang New Energy Technology Co., Ltd., carbon content ≥ 99wt%;

[0049] KH570 modified graphene oxide: add 2g of graphite oxide to a 250mL beaker and then add 30mL of deionized water and stir evenly; add 20mL of anhydrous ethanol to a 50mL beaker and then slowly add 1g of KH570 with a rubber-tipped dropper and stir to fully dissolve it; add the KH570 solution to the graphene oxide aqueous solution and ultrasonicate for 30min, then heat to 50℃ and react for 1 hour, heat to 70℃ and continue to react for 1 hour, cool to room temperature, centrifuge, wash 5 times, and remove unreacted KH570; take the precipitate after centrifugation, and air-dry it naturally in the air to obtain KH570 modified graphene oxide;

[0050] KH550 modified graphene oxide: add 2g of graphite oxide to a 250mL beaker and then add 30mL of deionized water and stir evenly; add 20mL of anhydrous ethanol to a 50mL beaker and then slowly add 1g of KH550 with a rubber-tipped dropper and stir to fully dissolve it; add the KH550 solution to the graphene oxide aqueous solution and ultrasonicate for 30min, then heat to 50℃ and react for 1 hour, heat to 70℃ and continue to react for 1 hour, cool to room temperature, centrifuge, wash 5 times, and remove unreacted KH550; take the precipitate after centrifugation, and air-dry it naturally in the air to obtain KH550 modified graphene oxide.

[0051] Example 1

[0052] This embodiment provides an ionic liquid inhibitor for warm water-based drilling fluid, wherein the raw materials for preparing the ionic liquid inhibitor include methionine, concentrated sulfuric acid and KH570-modified graphene oxide;

[0053] The amino acid is methionine, the mass concentration of concentrated sulfuric acid is 98%, and the organosilicon nanomaterial is graphene oxide modified by KH570;

[0054] The molar ratio of methionine to H2SO4 in concentrated sulfuric acid is 1:1;

[0055] The ratio between the amount of methionine and the mass of KH570-modified graphene oxide is 1 mol:3 g.

[0056] The preparation method of the above-mentioned ionic liquid inhibitor for temperature-resistant water-based drilling fluid is as follows:

[0057] Weigh methionine (1 mol) and place it in a round-bottom flask, add distilled water (180 mL) to dissolve it, add concentrated sulfuric acid (1 mol of H2SO4), place the reaction system in a 70°C constant temperature magnetic stirrer and stir to neutralize the reaction, after the temperature of the reaction system rises to 70°C, add KH570-modified graphene oxide (3 g) and react for 12 hours. After the reaction is completed, the synthetic product is fully washed with ethyl acetate 5 times, rotary evaporated and dried, and then placed in an electric blast constant temperature drying oven to dry to constant weight to obtain the temperature-resistant water-based drilling fluid ionic liquid inhibitor (Asp).

[0058] Example 2

[0059] This embodiment provides an ionic liquid inhibitor for warm water-based drilling fluid, wherein the raw materials for preparing the ionic liquid inhibitor include methionine, concentrated sulfuric acid and KH550-modified graphene oxide;

[0060] The molar ratio of methionine to H2SO4 in concentrated sulfuric acid is 1:1.1;

[0061] The ratio between the amount of methionine and the mass of KH550-modified graphene oxide is 1 mol:3 g.

[0062] The preparation method of the above-mentioned ionic liquid inhibitor for temperature-resistant water-based drilling fluid is as follows:

[0063] Weigh methionine (1 mol) and place it in a round-bottom flask, add distilled water (190 mL) to dissolve it, add concentrated sulfuric acid (1.1 mol of H2SO4), place the reaction system in a 70°C constant temperature magnetic stirrer and stir to neutralize the reaction, and after the temperature of the reaction system rises to 70°C, add KH550-modified graphene oxide (3 g) and react for 16 hours. After the reaction is completed, the synthetic product is fully washed with ethyl acetate 4 times, rotary evaporated and dried, and then placed in an electric blast constant temperature drying oven to dry to constant weight to obtain the temperature-resistant water-based drilling fluid ionic liquid inhibitor (Asp).

[0064] Example 3

[0065] This embodiment provides an ionic liquid inhibitor for warm water-based drilling fluid, wherein the raw materials for preparing the ionic liquid inhibitor include L-aspartic acid, concentrated sulfuric acid and KH550-modified graphene oxide;

[0066] The molar ratio of L-aspartic acid to H2SO4 in concentrated sulfuric acid is 1:1.2;

[0067] The ratio between the amount of L-aspartic acid and the mass of KH550-modified graphene oxide is 1 mol:4 g.

[0068] The preparation method of the above-mentioned ionic liquid inhibitor for temperature-resistant water-based drilling fluid is as follows:

[0069] L-aspartic acid (1 mol) was weighed and placed in a round-bottom flask, distilled water (200 mL) was added to dissolve it, concentrated sulfuric acid (1.2 mol of H2SO4) was added thereto, and the reaction system was placed in a constant temperature magnetic stirrer at 80°C and stirred for neutralization reaction. After the temperature of the reaction system was heated to 80°C, KH550-modified graphene oxide (4 g) was added thereto and reacted for 18 hours. After the reaction was completed, the synthetic product was fully washed with ethyl acetate for 6 times, rotary evaporated and dried, and then placed in an electric blast constant temperature drying oven to dry to constant weight to obtain the temperature-resistant water-based drilling fluid ionic liquid inhibitor (Asp).

[0070] Example 4

[0071] This embodiment provides an ionic liquid inhibitor for warm water-based drilling fluid, wherein the raw materials for preparing the ionic liquid inhibitor include L-aspartic acid, concentrated sulfuric acid and KH570-modified graphene oxide;

[0072] The molar ratio of L-aspartic acid to H2SO4 in concentrated sulfuric acid is 1:1.3;

[0073] The ratio between the amount of L-aspartic acid and the mass of KH570-modified graphene oxide is 1 mol:5 g.

[0074] The preparation method of the above-mentioned ionic liquid inhibitor for temperature-resistant water-based drilling fluid is as follows:

[0075] L-aspartic acid (1 mol) was weighed and placed in a round-bottom flask, distilled water (210 mL) was added to dissolve it, concentrated sulfuric acid (1.3 mol of H2SO4) was added thereto, and the reaction system was placed in a constant temperature magnetic stirrer at 80°C and stirred for neutralization reaction. After the temperature of the reaction system was heated to 80°C, KH570-modified graphene oxide (5 g) was added thereto and reacted for 20 hours. After the reaction was completed, the synthetic product was fully washed with ethyl acetate 5 times, rotary evaporated and dried, and then placed in an electric blast constant temperature drying oven to dry to constant weight to obtain the temperature-resistant water-based drilling fluid ionic liquid inhibitor (Asp).

[0076] Example 5

[0077] This embodiment provides an ionic liquid inhibitor for warm water-based drilling fluid, wherein the raw materials for preparing the ionic liquid inhibitor include methionine, concentrated sulfuric acid and KH570-modified graphene oxide;

[0078] The molar ratio of methionine to H2SO4 in concentrated sulfuric acid is 1:1.4;

[0079] The ratio between the amount of methionine and the mass of KH570-modified graphene oxide is 1 mol:5 g.

[0080] The preparation method of the above-mentioned ionic liquid inhibitor for temperature-resistant water-based drilling fluid is as follows:

[0081] Weigh methionine (1 mol) and place it in a round-bottom flask, add distilled water (230 mL) to dissolve it, add concentrated sulfuric acid (1.4 mol of H2SO4), place the reaction system in a 90°C constant temperature magnetic stirrer and stir to neutralize the reaction, after the temperature of the reaction system rises to 90°C, add KH570-modified graphene oxide (5 g) and react for 12 hours. After the reaction is completed, the synthetic product is fully washed with ethyl acetate 5 times, rotary evaporated and dried, and then placed in an electric blast constant temperature drying oven to dry to constant weight to obtain the temperature-resistant water-based drilling fluid ionic liquid inhibitor (Asp).

[0082] Example 6

[0083] This embodiment provides an ionic liquid inhibitor for warm water-based drilling fluid, wherein the raw materials for preparing the ionic liquid inhibitor include methionine, concentrated sulfuric acid and KH550-modified graphene oxide;

[0084] The molar ratio of methionine to H2SO4 in concentrated sulfuric acid is 1:1.5;

[0085] The ratio between the amount of methionine and the mass of KH550-modified graphene oxide is 1 mol:6 g.

[0086] The preparation method of the above-mentioned ionic liquid inhibitor for temperature-resistant water-based drilling fluid is as follows:

[0087] Weigh methionine (1 mol) and place it in a round-bottom flask, add an appropriate amount of distilled water (200 mL) to dissolve it, add concentrated sulfuric acid (1.5 mol of H2SO4), place the reaction system in a constant temperature magnetic stirrer at 80°C and stir to neutralize it, after the temperature of the reaction system rises to 80°C, add KH550-modified graphene oxide (6 g) and react for 12 hours. After the reaction is completed, the synthetic product is fully washed with ethyl acetate 5 times, rotary evaporated and dried, and then placed in an electric blast constant temperature drying oven to dry to constant weight to obtain the temperature-resistant water-based drilling fluid ionic liquid inhibitor (Asp).

[0088] Soil sample treated with Asp: Asp provided in this embodiment, montmorillonite (purchased from Xinjiang Zhongfei Xiazijie Bentonite Co., Ltd., the same below) and pure water were mixed for 20 minutes to obtain a mixture A, in which the mass concentration of Asp was 1% and the mass concentration of montmorillonite was 4%;

[0089] Mixture A was placed in a centrifuge at 4000 rpm for 10 min. After centrifugation, the supernatant was discarded and the remaining mud was placed in a clean beaker. It was then dried in an oven at 105±1°C for 24 h to obtain an Asp-treated soil sample.

[0090] Soil sample treated with pure water: Mix montmorillonite and pure water for 20 min to obtain mixture B. In mixture A, the mass concentration of montmorillonite is 4%;

[0091] Mixture B was placed in a centrifuge at 4000 rpm for 10 min. After centrifugation, the supernatant was discarded and the remaining mud was placed in a clean beaker. It was then dried in an oven at 105±1°C for 24 h to obtain an Asp-treated soil sample.

[0092] The infrared spectra of the soil samples treated with Asp and pure water were tested and characterized using a Nicolet 5700 Fourier transform infrared spectrometer from Thermo Fisher Scientific. Figure 1 As shown. Figure 1 It can be seen that the infrared spectrum of the water-treated soil sample has two strong absorption peaks in the high-frequency region, 3620.7cm -1 The characteristic peaks near this can be attributed to the stretching vibration of Al-OH, 3445.3 cm -1 The characteristic peaks near 1635cm -1 The strong characteristic peak near 1032.1cm can be attributed to the stretching vibration of HOH. -1 and 777.8cm -1 The characteristic peaks near can be attributed to the stretching vibration of Si-O-Si; the low frequency region is at 693cm -1 and 466cm -1 The strong absorption band at the bottom is considered to be caused by the coupling vibration of Si-OM and MO. From the infrared spectrum of the Asp-treated soil sample, it can also be seen that the main functional groups of the Asp inhibitor are adsorbed in montmorillonite, which indirectly indicates that its adsorption effect is obvious.

[0093] The thermal stability of the soil samples treated with Asp and pure water was analyzed using a TGA / DSC1 thermogravimetric analyzer from Mettler-Toledo. Figure 2 As shown. Figure 2It can be seen that: with the increase of temperature, the mass of the two soil samples decreased to a certain extent. When the temperature increased from 50℃ to 350℃, the mass of the soil sample treated with distilled water decreased to 95.78%, while the mass of the soil sample treated with Asp only decreased to 97.98%.

[0094] Unhydrated soil sample treated with Asp: The Asp and montmorillonite provided in this embodiment were stirred and mixed for 20 minutes, and dried in an oven at 105±1° C. for 24 hours to obtain an unhydrated soil sample treated with Asp, wherein the mass ratio of Asp to montmorillonite was 0.5:4;

[0095] Hydrated soil sample treated with Asp: After mixing Asp, montmorillonite and pure water provided in this embodiment for 20 minutes, a mixture C is obtained, in which the mass concentration of Asp is 0.5% and the mass concentration of montmorillonite is 4%;

[0096] The mixture C was centrifuged at 4000 rpm for 10 min. The supernatant was discarded and the remaining slurry was placed in a clean beaker. The mixture was then dried in an oven at 105±1°C for 24 h to obtain an Asp-treated soil sample.

[0097] Unhydrated soil sample: Place the montmorillonite in an oven and dry it at 105±1℃ for 24h to obtain an unhydrated soil sample;

[0098] Hydrated soil sample: Mix montmorillonite and pure water for 20 min to obtain a mixture D, in which the mass concentration of montmorillonite is 4%;

[0099] The mixture D was centrifuged at 4000 rpm for 10 min. The supernatant was discarded and the remaining mud was placed in a clean beaker. The mixture was then dried in an oven at 105±1°C for 24 h to obtain a hydrated soil sample.

[0100] The particle size of the unhydrated soil sample treated with Asp, the hydrated soil sample treated with Asp, the unhydrated soil sample, and the hydrated soil sample were analyzed using the LS13320 laser diffraction particle size analyzer produced by Beckman Coulter, USA. The particle size distribution diagram is shown in FIG. Figure 3 As shown. Figure 3 It can be seen that the average particle size of the unhydrated soil samples is 14.270μm, and the median particle size is 11.020μm; the average particle size of the hydrated soil samples is 7.903μm, and the median particle size is 4.660μm. After adding 0.5% Asp inhibitor, the average particle size of the unhydrated soil samples decreased by 6.726μm, and the median particle size decreased by 2.872μm; the average particle size of the hydrated soil samples increased by 0.282μm, and the median particle size increased by 2.101μm.

[0101] The Asp or KCl provided in this example, montmorillonite and pure water were mixed for 20 minutes to obtain mixtures D to I;

[0102] Mixture D to Mixture I were centrifuged in a centrifuge at 4000 rpm for 10 min, the supernatant was discarded, the remaining mud was placed in a clean beaker, and then dried in an oven at 105±1℃ for 24 h to obtain the following soil samples:

[0103] 1.0% KCl treated soil sample: prepared from mixture D, in which the mass concentration of KCl is 1% and the mass concentration of montmorillonite is 4%;

[0104] Soil sample treated with 0.1% Asp: prepared from mixture E, in which the mass concentration of Asp is 0.1% and the mass concentration of montmorillonite is 4%;

[0105] 0.2% Asp treated soil sample: prepared from mixture F, in which the mass concentration of Asp is 0.2% and the mass concentration of montmorillonite is 4%;

[0106] 0.3% Asp treated soil sample: prepared from mixture G, in which the mass concentration of Asp is 0.3% and the mass concentration of montmorillonite is 4%;

[0107] 0.5% Asp treated soil sample: prepared from mixture H, in which the mass concentration of Asp is 0.5% and the mass concentration of montmorillonite is 4%;

[0108] Soil sample treated with 1.0% Asp: prepared from mixture I, in which the mass concentration of Asp is 1% and the mass concentration of montmorillonite is 4%.

[0109] The linear expansion rate of soil samples treated with pure water, 1.0% KCl, 0.1% Asp, 0.2% Asp, 0.3% Asp, 0.5% Asp, and 1.0% Asp was analyzed using the NP-01 normal temperature and pressure expansion rate tester produced by Qingdao Haitongda Special Instrument Factory. The linear expansion rate test results are shown in the figure below. Figure 4 As shown. Figure 4 It can be seen that: with the gradual increase of Asp mass concentration, the linear expansion rate of the soil sample treated with ESP becomes lower, indicating that the inhibition performance of Asp gradually increases. When the mass concentration of Asp is 1%, the linear expansion rate of the soil sample treated with ESP is only 18.6%.

[0110] Soil sample treated with 6.0% KCl: KCl, montmorillonite and pure water were mixed for 20 minutes to obtain a mixture J, in which the mass concentration of KCl was 6.0% and the mass concentration of montmorillonite was 4%;

[0111] The mixture J was placed in a centrifuge at 4000 rpm for 10 min. After centrifugation, the supernatant was discarded and the remaining mud was placed in a clean beaker. It was then dried in an oven at 105±1°C for 24 h to obtain a soil sample treated with 6.0% KCl.

[0112] The linear expansion rate of soil samples treated with 6.0% KCl and 1.0% Asp was analyzed using the NP-01 normal temperature and pressure expansion rate tester produced by Qingdao Haitongda Special Instrument Factory. The linear expansion rate test results are shown in the figure below: Figure 5 As shown. Figure 5 It can be seen that the inhibition rate of the Asp solution with a mass concentration of 1.0% is much stronger than the inhibitor KCl commonly used in oil fields.

[0113] Example 7

[0114] This embodiment provides an ionic liquid inhibitor for warm water-based drilling fluid, wherein the raw materials for preparing the ionic liquid inhibitor include L-aspartic acid, concentrated sulfuric acid and organosilicon nanomaterials;

[0115] The organosilicon nanomaterial is a mixture of KH570-modified graphene oxide and KH550-modified graphene oxide (the mass ratio of the two is 1:1);

[0116] The molar ratio of L-aspartic acid to H2SO4 in concentrated sulfuric acid is 1:1.5;

[0117] The ratio between the amount of L-aspartic acid and the mass of the organic silicon nanomaterial is 1 mol:6 g.

[0118] The preparation method of the above-mentioned ionic liquid inhibitor for temperature-resistant water-based drilling fluid is as follows:

[0119] Weigh L-aspartic acid (1 mol) and place it in a round-bottom flask, add distilled water (210 mL) to dissolve it, add concentrated sulfuric acid (1.5 mol of H2SO4), place the reaction system in a constant temperature magnetic stirrer at 80°C and stir to carry out a neutralization reaction. After the temperature of the reaction system rises to 80°C, add nano-organic silicon material (6 g) and react for 24 hours. After the reaction is completed, the synthetic product is fully washed with ethyl acetate 6 times, rotary evaporated and dried, and then placed in an electric blast constant temperature drying oven to dry to constant weight to obtain the temperature-resistant water-based drilling fluid ionic liquid inhibitor (Asp).

[0120] Example 8-Example 9, Comparative Example 1-Comparative Example 2

[0121] Example 8-Example 9, Comparative Example 1-Comparative Example 2 respectively provide an ionic liquid inhibitor for warm water-based drilling fluid, which differs from Example 6 only in that:

[0122] In Example 8: the ratio between the amount of methionine and the mass of KH550-modified graphene oxide is 1 mol:3 g;

[0123] In Example 9: the ratio between the amount of methionine and the mass of KH550-modified graphene oxide is 1 mol:4 g;

[0124] In Comparative Example 1: the ratio between the amount of methionine and the mass of KH550-modified graphene oxide is 1 mol:2 g;

[0125] In Comparative Example 2: the ratio between the amount of methionine and the mass of KH550-modified graphene oxide is 1 mol:8 g;

[0126] Other conditions are the same as those in Example 6.

[0127] Comparative Example 3

[0128] This comparative example provides an ionic liquid inhibitor for warm water-based drilling fluid, which differs from Example 6 only in that: graphene oxide modified with KH550 is not used;

[0129] Other conditions are the same as those in Example 6.

[0130] Comparative Example 4

[0131] This comparative example provides an ionic liquid inhibitor for warm water-based drilling fluid, wherein the ionic liquid inhibitor is graphene oxide modified by KH550.

[0132] Comparative Example 5

[0133] This comparative example provides an ionic liquid inhibitor for warm water-based drilling fluid, which differs from Example 6 only in that the KH550-modified graphene oxide is replaced by an equal mass of aluminum oxide (D 50 The particle size was 8 nm and the purity was 99.99% (purchased from Hubei Huifu Nanomaterial Co., Ltd.). Other conditions were the same as those in Example 6.

[0134] The performance of the ionic liquid inhibitor for warm water-based drilling fluid provided in the above examples and comparative examples was tested, and the specific testing method is as follows:

[0135] The soil sample (purchased from Xinjiang Zhongfei Xiazijie Bentonite Co., Ltd.) was treated with the ionic liquid inhibitor for warm water-based drilling fluid provided by the above embodiments and comparative examples, and the specific treatment was as described above.

[0136] Clay mass retention rate: Using a TGA / DSC1 thermogravimetric analyzer from Mettler-Toledo, the thermal stability of the soil samples before and after treatment (24 h) with the ionic liquid inhibitor for the warm water-based drilling fluid provided in this embodiment was analyzed to obtain the clay mass retention rate;

[0137] Increase in median particle size of hydrated soil samples: Using the LS13320 laser diffraction particle size analyzer of Beckman Coulter, Inc., the particle size of the soil samples before and after being treated with the ionic liquid inhibitor for the temperature-resistant water-based drilling fluid provided in the above embodiments and comparative examples was analyzed to obtain the increase in median particle size of the hydrated soil samples;

[0138] Inhibition rate: The temperature-resistant water-based drilling fluid ionic liquid inhibitor provided in the above embodiments and comparative examples was mixed with water to obtain a base slurry with a mass concentration of 1.0%. The linear expansion rate of the base slurry was analyzed using the NP-01 normal temperature and pressure expansion rate tester produced by Qingdao Haitongda Special Instrument Factory to obtain the inhibition rate.

[0139] The above performance test data are shown in Table 1 below:

[0140] Table 1

[0141]

[0142]

[0143] As can be seen from the above content, the present invention designs the raw materials for preparing the ionic liquid inhibitor, further uses organic silicon nanomaterials, controls the dosage of amino acids, acidic compounds and organic silicon nanomaterials within a specific range, and synergistically improves the temperature of the organic silicon nanomaterials and ionic liquids to simultaneously enhance the clay mass retention rate and inhibition of the ionic liquid inhibitor, thereby preparing an ionic liquid inhibitor with both high clay mass retention rate and high inhibition, wherein the clay mass retention rate is 92.19%-98.37%, the inhibition rate is 16.8%-21.3%, and the increase in the median particle size of the hydrated soil sample is 2.092μm-2.452μm.

[0144] If the ratio between the amount of amino acid and the mass of organosilicon nanomaterial in the raw materials for preparing the ionic liquid inhibitor is too large (Comparative Example 1) or too small (Comparative Example 2), the comprehensive performance of the prepared ionic liquid inhibitor is poor.

[0145] If the raw materials for preparing the ionic liquid inhibitor do not contain organosilicon nanomaterials (Comparative Example 3), or only organosilicon nanomaterials are used as ionic liquid inhibitors (Comparative Example 4), or the organosilicon nanomaterials are replaced with aluminum oxide (Comparative Example 5), the comprehensive performance of the prepared ionic liquid inhibitor is also poor.

[0146] In summary, the present invention designs the raw materials for preparing the ionic liquid inhibitor, further uses organosilicon nanomaterials, controls the dosage of amino acids, acidic compounds and organosilicon nanomaterials within a specific range, and synergistically improves the temperature of the organosilicon nanomaterials and ionic liquids, thereby simultaneously enhancing the clay mass retention rate and inhibition of the ionic liquid inhibitor, and thus preparing an ionic liquid inhibitor with both high clay mass retention rate and high inhibition.

[0147] The applicant declares that the present invention illustrates the detailed process flow of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed process flow, that is, it does not mean that the present invention must rely on the above-mentioned detailed process flow to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. An ionic liquid inhibitor, characterized in that The raw materials for preparing the ionic liquid inhibitor include amino acids, acidic compounds and organosilicon nanomaterials; The acidic compound includes H2SO4; The molar ratio of the amino acid to the acidic compound is 1:(1-1.5); The ratio between the amount of the amino acid and the mass of the organosilicon nanomaterial is 1 mol:(3-6) g.

2. The ionic liquid inhibitor according to claim 1, characterized in that The amino acids include and / or 3. The ionic liquid inhibitor according to claim 1 or 2, characterized in that The organosilicon nanomaterial includes graphene oxide modified by a silane coupling agent, preferably graphene oxide modified by KH570 and / or graphene oxide modified by KH550.

4. The ionic liquid inhibitor according to any one of claims 1 to 3, characterized in that The molar ratio of the amino acid to the acidic compound is 1:1.

5.

5. The ionic liquid inhibitor according to any one of claims 1 to 4, characterized in that The ratio between the amount of the amino acid and the mass of the organosilicon nanomaterial is 1 mol:6 g.

6. A method for preparing the ionic liquid inhibitor according to any one of claims 1 to 5, characterized in that: The preparation method comprises the following steps: After the amino acid and the solvent are mixed, an acidic compound is added thereto to carry out a neutralization reaction. After the temperature of the reaction system is raised to the neutralization reaction temperature, an organosilicon nanomaterial is added thereto to react and obtain the ionic liquid inhibitor.

7. The preparation method according to claim 6, characterized in that: The solvent is water; Preferably, the ratio between the amount of the amino acid substance and the volume of the solvent is 1 mol: (180-240) mL.

8. The preparation method according to claim 6 or 7, characterized in that: The temperature of the neutralization reaction is 70-90°C, preferably 80°C; Preferably, the neutralization reaction time is 12-24 hours, more preferably 12 hours.

9. The preparation method according to any one of claims 6 to 8, characterized in that: The reaction also includes a post-treatment step, and the post-treatment method includes: washing and drying; Preferably, the solvent used in the washing process comprises ethyl acetate; Preferably, the washing is performed 4-6 times.

10. A use of the ionic liquid inhibitor according to any one of claims 1 to 5, characterized in that: The ionic liquid inhibitor is used to prepare temperature-resistant water-based drilling fluid; Preferably, the mass percentage of the ionic liquid inhibitor in the temperature-resistant water-based drilling fluid is 0.1-1%.